Rice Sufficiency Officers’ Role Perception and Job Satisfaction as Agricultural Research and Extension Workers - Irene R. Tanzo; Charmaine G Yusongco (Journal of International Agricultural and Extension Education, 2014)
The study determined how the Rice Sufficiency Officers (RSOs) perceived their role and their level of job satisfaction when working as agents of PhilRice to promote and deliver rice technologies as a strategy to attain rice self-sufficiency for the country. Data for the study were collected using online survey to which77 RSOs responded. Results of the study showed the RSOs perceived their role as very important, particularly the extension tasks they fulfilled. Their level of job satisfaction was very high, especially with their working relationships with supervisors and the farmers. However, their status of employment caused some degree of dissatisfaction. Results shed light on issues concerning development programs of the institute.
Keywords: Job Satisfaction; Role Perception; Rice; RSO; Likert Scale